INTRODUCING EDUCATION BASED ON HUMAN RIGHTS IN HIGHER EDUCATION: EXAMPLES FROM A LANGUAGE SUBJECT - MartÃnez Lirola, MarÃa (International Journal of Education, 2017)
Despite the progress that has been carried out in different areas of society in recent years, human rights are still violated in various ways in different parts of the world. This article chooses an educational proposal based on human rights in order to assert their importance through various practical activities carried out in higher education, particularly in a compulsory subject of the degree in English Studies in a Spanish University. The purpose of the chosen activities is that students reflect on human rights so that they can improve their critical awareness and their commitment in defending them. This educational proposal combines the development of the different skills requested in a language subject (listening, speaking, reading, writing and interaction), the acquisition of values and the importance of human rights. The proposed activities contribute to students’ progress as active, critical, ethical and committed citizens, who are able to become aware of the different ways in which human rights are violated. Moreover, they are able to provide coherent responses based on the approach that has been followed in the teaching-learning process. Therefore, it is concluded that the educational approach presented in this article is suitable for students to be sensitized, to develop social awareness, and to acquire different skills.